Assessment and feedback practices in the EFL classroom - Ida Ayu Made Sri Widiastuti (Universitas Negeri Yogyakarta, 2021)
The present study explored the implementation of Language classroom assessment and feedback within the English as a Foreign Language (EFL) classroom. This research was conducted using a qualitative research design, and the obtained data were analyzed descriptively. Data were collected by conducting direct classroom observation using observation checklists and in-depth interviews with the three professional English instructors using an observation guide. The data were transcribed and coded according to their categories. The findings of the study indicated that the students learning progress were assessed through a short question-answer and completion test. Verbal feedback was merely provided by the teachers, and feedback was given only occasionally. The teacher hardly provided any follow-up action in order to modify their way of teaching. Consequently, there was a slow, gradual improvement of the students' learning achievement. Therefore, teachers were recommended to utilize various classroom language assessments to assess the students' learning. The teachers should provide both verbal and written feedback for their students to enhance their achievement continually.